Application of unmanned aerial vehicles in civil protection - Ljubljanović, Aleksandar; Draganić, Stjepan; Vinković, Mladen (Crisis Management Days, 2025)
Unmanned Aerial Vehicles (UAVs) have become essential tools in civil protection due to their capabilities in rapid data collection, access to hard-to-reach areas, and reducing risks to human life. This paper analyzes the applications, technical characteristics, challenges, and regulatory frameworks of UAVs in civil protection, as well as their roles in crisis situations. 1. Introduction to UAVs and Their Applications UAVs, commonly known as drones, are aircraft without onboard pilots, operated remotely or autonomously via programmed routes and advanced navigation systems. Over recent decades the development of UAV systems has significantly enhanced their applications beyond the military sector, extending into civil operations such as agriculture, surveying, infrastructure monitoring, and crisis management. In civil protection systems, UAV applications include: Rapid situation assessment and real-time data collection. Terrain mapping and modelling post-disasters. Detection of hazardous substances. Delivery of emergency supplies. Establishment of communication networks. Coordination of rescue operations and reduction of exposure risks for civil protection personnel. 2. Technical Characteristics of UAV Systems UAVs utilize various technologies that enable high levels of autonomy, precision, and operational flexibility. Key components of UAV systems include: Navigation Systems Global Navigation Satellite Systems (GNSS): Systems like GPS, GLONASS, Galileo, and BeiDou provide precise positioning for UAVs.​ Inertial Navigation Systems (INS): These systems use sensors (accelerometers and gyroscopes) to track UAV movements.​ Real-Time Kinematic (RTK) GNSS: This technology offers high-precision positioning, crucial for terrain mapping.​ Sensor Equipment Optical Sensors: High-resolution cameras for aerial imaging and surveillance.​ LIDAR (Light Detection and Ranging): Laser systems for precise 3D mapping.​ Thermal Cameras: Detection of heat sources in search and rescue operations.​ Gas and Radiation Sensors: Collect environmental data on hazardous substances.​ Data Transmission Radio Frequency (RF) Systems: Standard communication between UAVs and operators.​ Satellite Communication: Enables operations over long distances.​ 5G Networks and Mesh Systems: Provide low latency and real-time data transmission.​ 3. Regulatory and Safety Aspects Legal regulations and standards play a crucial role in the safe integration of UAVs into civil protection systems. International regulations, such as those from the International Civil Aviation Organization (ICAO) and the European Union Aviation Safety Agency (EASA), define guidelines for the safe use of unmanned systems. In the Republic of Croatia, applicable regulations include: The Air Traffic Act and EU Regulations 2019/945 and 2019/947. Rules on aerial operations and aerial photography, regulating drone use for civil purposes. Safety protocols, including operator training, UAV registration, and airspace restrictions. 4. UAV Applications in Civil Protection Rapid Situation Assessment and Data Collection UAVs provide real-time visual information about affected areas. For example, during the 2020 earthquake in Petrinja, UAV systems were used to assess damages and evaluate the stability of structures.​ Terrain Mapping and Modeling Post-natural disasters, UAVs assist in creating orthophoto maps and 3D terrain models, facilitating planning for rehabilitation and resource distribution.​ Detection of Hazardous Substances UAVs equipped with chemical and radiological sensors can identify hazardous gases, air pollution, and radiation in real-time, enabling timely responses from civil protection forces.​ Delivery of Emergency Supplies In isolated areas, UAVs can deliver medical supplies, food, and communication equipment where traditional vehicles are impeded.​ 5. Case Studies Fire at Drava International (2023) UAVs were used to monitor a fire at a plastic waste warehouse in Osijek. Equipped with thermal cameras, they assisted firefighters in identifying hotspots and coordinating interventions.​ Fire at Lagermax Warehouse (2024) Following the fire, UAVs were utilized to create 3D models of the burned area, enabling investigators to conduct detailed analyses and assist in the investigation.​ Use of Drones after Ice Storms in Bošnjaci After a devastating ice storm, UAVs supported damage assessments on roofs and infrastructure, facilitating the identification of damages and monitoring rehabilitation efforts.​ 6. Challenges and Future Trends The main challenges in using UAVs in civil protection include: Limited flight duration and the need for better batteries. Security threats, including cyber-attacks. Regulatory obstacles and the need for legal harmonization. Integration of UAVs with other crisis management systems. Future developments will focus on enhancing autonomy, using artificial intelligence for data analysis, and increasing the integration of UAVs among civil protection operational forces. Conclusion UAVs represent key technology for modernizing civil protection systems. Their ability to rapidly collect data, access hard-to-reach areas, and enhance the safety of operational personnel contributes to more effective responses to crisis situations. Further integration of UAVs, along with improvements in regulations and the development of advanced data analysis systems, will enable their broader and more efficient application in civil protection systems.